Is equity meaningfully incorporated into pandemic preparedness and response? A scoping review and critical analysis of Ebola andCOVID-19 outbreak responses in Uganda 2019-2023 - Redondo G; Murray L; Bromhead C; Makumbi I (Taylor and Francis Group, 2025)
Societal inequities produce vulnerabilities that infectious disease can exploit. Current approaches to pandemic prevention, detection and response are led by the International Health Regulations IHR and the Global Health Security Agenda. However, to contain the spread of infectious diseases, localised action to address systemic inequities must be considered. The purpose of this scoping review and equity analysis is to 1) Synthesise the available information on Uganda’s Ebola Virus Disease (EVD) and COVID-19 preparedness and outbreak responses between 2019 and 2023, and 2) Critique if and how Uganda’s Ministry of Health incorporated concepts of health equity in its EVD and COVID-19 interventions, while building national capacity to identify and prevent public health emergencies. This scoping review and critical analysis was conducted following the five-stage process defined by Levac et al. After identification and screening, the scoping review was based on six preparedness and response plans, three after-action reviews, and 20 grey literature and peer-reviewed articles. The findings revealed that the EVD and COVID-19 preparedness and response plans in Uganda show the country’s commitment and readiness for early detection and response to infectious disease outbreaks. However, further examination of the plans reveals missed opportunities to address systemic inequities. The ongoing mpox outbreak, declared a PHEIC by WHO on July 23, 2022, with significant impacts in African countries including Uganda, further underscores the need for a paradigm shift in managing infectious disease outbreaks. Such a shift may be similar to that experienced by the field of disaster risk reduction, which underwent a significant transformation at the Sendai Conference in 2015 towards a more holistic and proactive approach that addresses underlying systemic issues and focuses on building resilience. The exclusive focus on biomedical strategies to manage infectious diseases fails to address the social aspects of transmission, the local perceptions of illness, and community vulnerabilities often associated with social and historical perspectives. The social determinants of health disparities should be incorporated into pandemic planning and response. This will contribute to fostering equitable health outcomes and resilience in the face of the multifaceted challenges posed by future pandemics and environmental changes.
Keywords: Africa; infectious disease prevention; pandemic; equity; Uganda; disaster risk reduction